Serum levels of IL-6 and CRP can predict the efficacy of mFOLFIRINOX in patients with advanced pancreatic cancer - Shen, Feifei; Liu, Chuan; Zhang, Weiguo; He, Sijia; Wang, Fan; Wang, Jingjue; Li, Qi; Zhou, Fei (Frontiers in Oncology, 2022)
Objectives There is an urgent need for biomarkers that predict the survival outcome of patients diagnosed with metastatic pancreatic cancer, undergoing systemic chemotherapy. This study aimed to identify biomarkers associated with the survival of mPC patients treated with modified FOLFIRINOX (mFOLFIRINOX) as first-line chemotherapy. Methods This was a retrospective study of 30 patients with mPC who received mFOLFIRINOX between October 2018 and March 2021. Data on carcinoembryonic antigen (CEA), cancer antigen (CA)199, interleukin (IL)-6, C-reactive protein (CRP), neutrophils, platelets, lymphocytes, and albumin were collected and dichotomized using the upper or lower limit, as appropriate. These markers were examined for their association with progression-free survival (PFS). A receiver operating characteristic (ROC) curve analysis was used to explore a suitable model to predict mFOLFIRINOX effectiveness. Results IL-6 and CRP levels were associated with poor progression (P = 0.004 and P = <0.001, respectively) of mPC. The high IL-6 level was an independent poor prognostic factor for PFS (HR=4.66, 95%CI: 1.32-16.37, P=0.016) in the multivariable analysis. Patients with high IL-6 levels had a shorter PFS than those with low IL-6 levels (median PFS: 257 vs. 150 days, P=0.020). An increase in IL-6 and CRP levels during chemotherapy positively correlated with disease progression (P = <0.001 for both). The model combining IL-6 with CRP levels helped predict the outcomes of mPC patients treated with mFOLFIRINOX (AUC: 0.811, 95%CI: 0.639-0.983, P=0.003). Conclusions The serum levels of IL-6 and CRP might be considered as valuable biomarkers in predicting the outcomes of patients with mPC who received the mFOLFIRINOX regimen.